VD_FINDINFO Arrêt / 2009 / 750 vom 9. Dezember 2009 - VD Tribunal cantonal (2009)
MESURE D'INSTRUCTIONASSURANCE SOCIALE, FORCE PROBANTE, DÉCISION DE RENVOI, RÉVISION DE LA RENTE, AIASSURANCE | 1 LAI, 57 LAI, 17 LPGA, 56 LPGA, 57 LPGA, 61 LPGA, 69 RAI, 87 al. 3 RAI, 2 LPA-VD, 52 LPA-VD, 55 al. 1 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. a LPA-VD